Community Preceptors' Motivations and Views about Their Relationships with Medical Students During a Longitudinal Family Medicine Experience: A Qualitative Case Study. Issue 2 (15th March 2019) - Rodríguez, Charo; Bélanger, Emmanuelle; Nugus, Peter; Boillat, Miriam; Dove, Marion; Steinert, Yvonne; Lalla, Leonora
Abstract: Phenomenon : Although current evidence emphasizes various benefits of community-oriented programs, little is still known about the nature of the relationships that students and family physicians develop in this educational setting. Our aim in this study was twofold: to identify family physicians' motivations to enroll as preceptors in a longitudinal undergraduate family medicine program and to explore the nature of the student–preceptor relationships built during the course. Approach : This was a qualitative exploratory case study. The case was the first edition of a longitudinal family medicine experience (LFME), a course that makes up part of the novel Medicinae Doctor et Chirurgiae Magister curriculum in place in a Canadian medical school since August 2013. All 173 family physician community preceptors of the academic year 2013–2014 were considered key informants in the investigation. Forty-three preceptors finally participated in one of six focus groups conducted in the spring of 2014. Several organizational documents relative to the LFME course were also gathered. Inductive semantic thematic analysis was performed on verbatim interview transcripts. Documents helped contextualize the major themes emerging from the focus groups discussions. Findings : Enjoying teaching, promoting family medicine, and improving medical education where salient motivations for family physicians to become LFME preceptors. The findings also pointed out the complexity of the student–preceptor exchanges that unfolded over the academic year, and the ambiguous and changing nature of the role that LFME preceptors adopted in their relationships with students: from simply being facilitators of students' clinical observership to behaving as their mentors. Insights : Family physicians were highly motivated to become LFME preceptors of 1st-year medical students. Whereas they consistently valued the relationships built during the academic year with the students assigned to them, they also considered that exchanges did not always happen without difficulties, and gauged the roles they played as complex, ambiguous, and necessarily evolving over time.